Electrochemical studies on the reduction behaviour of Th4+ in molten LiCl-KCl eutectic. (10th February 2015) - Pakhui, Gurudas; Chandra, Manish; Ghosh, Suddhasattwa; Reddy, B. Prabhakara; Nagarajan, K.
Graphical abstract: Abstract: The electrochemistry of Th 4+ ions was studied in LiCl-KCl eutectic in the temperature range 698–803 K and compared with literature data. Various transient electrochemical techniques like cyclic voltammetry, chronopotentiometry, square-wave voltammetry were used to determine diffusion co-efficient of Th 4+ and apparent standard electrode potential for Th 4+ /Th electrode process. The electrode kinetics of Th 4+ /Th couple was also investigated by convolution voltammetry and impedance spectroscopy. Based on the above studies, the reversibility of Th 4+ /Th couple was addressed. The feasibility of electrochemical separation of uranium and thorium in LiCl-KCl eutectic is also discussed in this paper. It was seen that the separation of U from Th matrix was difficult in molten LiCl-KCl using a solid rod cathode and suitable reactive electrodes need to be used for efficient separation.